Digital Transformation of EU Customs: eCommerce VAT Legislation and a Proposed Customs Clearance Application - Irene Gkoni; Maria Rigou; Georgios Thanasas; Stefanos Balaskas (Emerging Science Journal, 2024)
In the digital world, borders between countries are fading, and many people keep making more and more online purchases, often from offshore vendors. Cross-border e-commerce is a game-changer for international trade but poses serious challenges for traditional customs procedures. As the number of parcels continues to grow rapidly, customs authorities around the world strive to balance between effective revenue collection, trade facilitation, and proper safety controls. At the EU level, significant revenue losses and competition distortion have led to changes in VAT rules with a key policy objective to fight tax fraud in e-commerce and reduce the administrative burden of VAT collection. The VAT e-commerce package that came into force on July 1, 2021, includes measures on imports of low-value goods from third countries. The adopted solution imposes liability on digital platforms that play a crucial role in the rise of B2C internet sales. This article provides an overview of e-commerce global trends and challenges, international organizations’ initiatives, emerging technology pilots, as well as best practices. It also offers a critical description of the new EU VAT provisions that have a severe effect on customs. Moreover, it describes the design, functional, and interoperability specifications of a proposed web-based application that enables buyers to lodge customs declarations themselves, aiming for improved transparency on import-related charges and more effective e-government at a more general level through the digital transformation of customs clearance. Doi: 10.28991/ESJ-2024-08-01-024 Full Text: PDF